2011
DOI: 10.1071/an10286
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for the conservation of the pudu (Pudu puda) in southern South America

Abstract: The southern pudu (Pudu puda) is a threatened deer that is endemic to the South American temperate forests. Despite its assumed threatened status, there is relatively little understanding on the ecology and conservation of this species. Considering this situation and the fact that there are some research groups currently working on this species, we organised a symposium to discuss research and management priorities – as well as to coordinate efforts – to move forward on the conservation of the pudu. We agreed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Specifically in the order Artiodactyla (Pudu puda) the opposite was true, being females the highest proportion of admitted animals. Female pudus take many months per year to produce and rear their offspring, with high gestation and lactation energy costs [20], making them more vulnerable to threats [21].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in the order Artiodactyla (Pudu puda) the opposite was true, being females the highest proportion of admitted animals. Female pudus take many months per year to produce and rear their offspring, with high gestation and lactation energy costs [20], making them more vulnerable to threats [21].…”
Section: Discussionmentioning
confidence: 99%
“…The conservation of a rare species is a difficult task considering the lack of information about current and potential habitats or habitat requirements [ 19 ]. Subsequently, predictive models, such as niche-based modeling, can be useful for obtaining reliable distribution maps to assess the suitability of proposed sites for conservation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is considered to be due the fact that temperature increase can negatively influence the quality and productivity of vegetation that maintains equilibrium in terrestrial ecosystems (Klein et al 2007). In addition to the combined effect of these environmental variables on the future distribution of the Pudu deer, we must consider the process of native forest loss occurring in the southern-central Chile due to anthropogenic activities, given that this variable plays a key role in the conservation of the species (Silva-Rodríguez et al 2011). It has been suggested that the net loss of native forest was lower in recent years compared to the 1970-1990 period (Smith- Ramírez 2004;Miranda et al 2017).…”
Section: Discussionmentioning
confidence: 99%